Effects of Achievement Motivation Training on a Group of Secondary School Students - Chuah, Kim Lian (1995)
This study examined the effects of achievement motivation training on a group of secondary school students. The training programme was developed based on activities adapted from the McClelland's tradition. It comprised 10 activities carried out in five sessions with each session lasting two and a half hours. Two Form Four classes were requested from the school authority. A total of 70 subjects (N=70) were randomly assigned into two groups based on the pre-test score of need for achievement measured by the Thematic Apperception Test. Treatment in the form of training was given to the first group of 35 Fourth Formers, whilst another group of 35 Fourth Formers formed the control group which received no treatment. Findings from the study showed that after training, subjects improved in their achievement motivation, locus of control and academic performance of Mathematics in the intended direction. However, results from Analysis of Covariance did not show that there were any significant differences in need for achievement, locus of control and academic performance in Mathematics between the trained and the untrained subjects.